Dataset of REFIR and NAME simulations of the Eyjafjallajokull 2010 eruption - Fabio Dioguardi; Frances Beckett; Tobias Dürig; John A. Stevenson (Zenodo, 2020)
This data set includes supporting data for the manuscript "The impact of eruption source parameter uncertainties on ash dispersion forecasts during explosive volcanic eruptions" submitted to Journal of Geophysical Research - Atmospheres. The data sets consists of 3 folders: elaborated_data, NAME_simulations and REFIR_simulations. 1) elaborated_data. This folder includes data mainly used to compare eruption source parameters time series produced by REFIR in the four simulation configurations (all models, Mastin only, only wind models, only empirical models). Specifically: radar_iskef.xlsx. Time series of the Eyjafjallajokulltop plume height (maximum and minimum estimate) retrieved from the C-band radar in Keflavík, Iceland. The time series is limited to the period 5/05/2010 (00:00UTC) to 8/05/2010 (23:55 UTC). The original time series is stored in the REFIR simulation folders as radar_iskef.txt. PLH.txt. Time seriesf the Eyjafjallajokulltop plume height (average, maximum and minimum solutions) as assessed by REFIR. cases_comparisons_FMER.txt. Time series of the final estimate of Mass Eruption Rate (FMER) for the four configurations and calculations for comparisons discussed in the manuscript. Weather_data_summary.xlsx. Time series of the weather parameters assessed by REFIR for the three estimates of the top plume heights. 2) NAME_simulations. This folders includes results (both raw data and plots) of NAME simulations for the four simulation configurations and for each estimate of the eruption source parameters (average, maximum and minimum). 3) REFIR_simulations. This folders includes input data andresults (both raw data and plots) of REFIR simulations for the four simulation configurations. The input data include the original and elaborated ERA-Interim weather data for the period 5-8 May 2010 in the folder "raw_reanalysis_weather_data_20100505".